Mapping the Research Landscape of Library Management Based on Artificial Intelligence: A Bibliometric Analysis - gema rullyana; Majidah; Rahmat Fadhli; Rifa Nadila (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2026)
Background of the study: The rapid advancement of artificial intelligence (AI) has spurred growing scholarly interest in its application to library management. Analyzing research trends in this area is essential to understand its intellectual development and identify emerging themes and future directions. Purpose: This study aims to map the research landscape of Library Management Based on AI through a bibliometric analysis. Method: Data were analyzed using Biblioshiny in RStudio and examined through performance analysis and science mapping techniques. Findings: The field shows publication growth, with an average annual growth rate of 40.04%. The highest publication volume occurred in 2021, followed by renewed growth in 2025. China emerged as the most productive and most cited country. Journal of Physics: Conference Series was the most productive source, while Library Hi Tech recorded the highest citation impact. Keyword analysis shows a shift from data mining and library automation toward deep learning, natural language processing, smart libraries, blockchain, Internet of Things, and data privacy. Conclusion: This study contributes to understanding the intellectual structure of artificial intelligence-based library management and highlights future needs for governance, ethics, privacy protection, institutional readiness, and human resource capacity